Gambaran Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa Sekolah Dasar Negeri Tengklik - Nova Riza Nuraini; Fitriana Noor Khayati; Chori Elsera; Ratna Agustiningrum (TRIAGE Jurnal Ilmu Keperawatan, 2026)
Clean and Healthy Living Behavior (PHBS) is a series of actions aimed at maintaining health. The spread of enteric germs, along with habits such as not washing hands before meals and after defecation, can allow bacteria to enter the body through food, leading to diseases such as diarrhea and worm infections among school-age children. This study aimed to describe the implementation of PHBS among students at Tengklik Public Elementary School. A descriptive quantitative cross-sectional method was employed. The sample consisted of 63 students from grades IV, V, and VI, selected through simple random sampling. The research instrument was a questionnaire with 28 statements, and data were analyzed using mean, minimum, maximum, and frequency distribution. The findings showed that 61.9% of students demonstrated good clean and healthy living behavior. Specifically, students reported high compliance in washing hands with soap before and after meals (90.5%), proper use of clean and healthy latrines (68.3%), exercising regularly (63.5%), not smoking at school (49.2%), disposing of waste properly (93.7%), and participating in community service activities (92.1%). However, some behaviors were only moderate, including consuming healthy food (65.1%) and eradicating mosquito larvae (58.7%). It can be concluded that the general characteristics of respondents were ages 10–13 years, with the majority being female (40 students) and most coming from grade VI (22 students). Overall, most students at Tengklik Public Elementary School had implemented Clean and Healthy Living Behavior with a prevalence of 61.9%.